Diversity in Vertical Structures of Internal Tide Dissipation Rate Around the Indonesian Throughflow Exits Simulated by a High‐Resolution Nonhydrostatic Model. Issue 9 (9th May 2021) - Wen, Xixi; Peng, Shiqiu; Qian, Yu‐Kun; Li, Yineng
Abstract: The vertical structure of internal tide dissipation rate ϵ is essential to the parameterization of the internal tide‐induced mixing, yet its diversity has always been oversimplified in ocean circulation models. Based on a high‐vertical‐resolution (10 m) simulation around the exits of the Indonesian throughflow, the diversity in ϵ profiles near both the bottom and the thermocline was investigated by a hierarchical clustering classification. Five typical near‐bottom vertical structures of ϵ were found, of which the bottom‐intensified structure is dominant. From the maximum dissipation depths to the shallower water, all five profiles obey the same decaying function. There are three typical near‐thermocline structures of ϵ: one menifests the thermocline‐intensified pattern and the other two feature a surface‐intensified pattern characterized by a monotonic increase from 500‐m depth to the surface. All three vertical structures near thermocline could be scaled by the reciprocal of the Richardson number. Plain Language Summary: Tidal currents flow over the uneven seafloor back and forth every day, causing mixing between adjacent vertical layers in the ocean. This process, known as tidal mixing, occurs in the whole ocean and is strong around the exits of the Indonesian throughflow (ITF). The vertical distribution of the tidal mixing is one of the primary elements that shapes the profiles of temperature and salinity and modulates the transports in the Indonesian seas. Previous studies suggested that tidal mixing is intensified at the bottom and the thermocline without considering its diversity in the real ocean. The diversity in the profiles of the tidal mixing around the exits of the ITF is explored. We found that, adjacent to the bottom topography, the mixing is intensified not only at the bottom but also at depths of hundreds of meters above the bottom and all of profiles obey the same decaying law from the maximum mixing depths to the shallower water. Near the thermocline, the tidal mixing is thermocline‐intensified away from the archipelago and surface‐intensified near the archipelago. These findings shed light on the vertical structures of tidal mixing in the ocean and are potentially valuable to improve the performance of ocean circulation models. Key Points: Diversity in the profiles of tide‐induced dissipation rate around the exits of the Indonesian throughflow is investigated Five typical profiles are revealed near the bottom, obeying the same decaying law from the maximum dissipation depths to shallower water Three typical profiles near the thermocline are also revealed, all of which can be scaled with the reciprocal of the Richardson number